Drivers of, barriers to, and facilitators of blood donation - Syadiyah Abdul Shukor,; Nur Shahira Mohamad Nor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to investigate drivers of, barriers to, and facilitators of blood donation among Muslim young adults in Malaysia who include both donors and non-donors. Using convenience sampling, 300 Muslim college students in Malaysia were invited to participate in this study. To assess differences between donors and non-donors’ blood-donation drivers, barriers, and facilitators, a chi-square test of independence and independent samples t-test were conducted. A total of 198 respondents participated (74.7% female, 87.9% aged between 18 and 24 years, 62.1% non-donors). Females were more likely than males to have experience with donating blood. Also, donors showed a higher mean score of drivers to donate blood, while non-donor revealed a higher mean score in terms of barriers to and facilitators of blood donation. This finding suggests that to encourage non-donors among Muslim young adults in Malaysia to donate blood, barriers that prevent them from doing so should be addressed.